2019
DOI: 10.1002/elps.201900319
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bicarbonate, phosphate and other anions in saliva by capillary electrophoresis with capacitively coupled contactless conductivity detection in diagnostics of gastroesophageal reflux disease

Abstract: Bicarbonate and phosphate constitute major salivary buffering components, and their importance consists in the neutralization of acidic gastric contents during reflux episodes. In this work, capillary electrophoresis with capacitively coupled contactless conductivity detector was applied for the analysis of bicarbonate, phosphate, and another inorganic (chloride, nitrite, nitrate, sulfate, thiocyanate) and organic anions (acetate, butyrate) to evaluate their levels in saliva. The background electrolytes of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Salivary bicarbonate was significantly higher in GERD patients than in other study groups. These results were agreed with other studies that found there was significant elevation in bicarbonate levels in patients with GERD group than healthy subjects [30]. Another study showed that salivary bicarbonate secretion was stimulated by esophageal acid perfusion in dose-dependent manner and this response protects the esophageal mucosa from acid injury [31].…”
Section: Laboratory Findingssupporting
confidence: 92%
“…Salivary bicarbonate was significantly higher in GERD patients than in other study groups. These results were agreed with other studies that found there was significant elevation in bicarbonate levels in patients with GERD group than healthy subjects [30]. Another study showed that salivary bicarbonate secretion was stimulated by esophageal acid perfusion in dose-dependent manner and this response protects the esophageal mucosa from acid injury [31].…”
Section: Laboratory Findingssupporting
confidence: 92%
“…Another condition, gastroesophageal reflux disease, is caused by reflux of gastric acid into the esophagus and can cause heartburn and, in severe cases, can lead to esophageal damage. Salivary HCO 3 – plays an important role in esophageal acid defense [225] , [226] , [227] by neutralizing gastric acid [228] . Conversely, the action of NHE1 in esophageal epithelia may exacerbate the damage, perhaps by indirectly stimulating pro-apoptotic pathways [229] .…”
Section: Applications By Organ Systemmentioning
confidence: 99%
“…No difference was reported in the concentrations of phosphate and other measured anions (6.4mM vs 5.7 mM; p=0.272) Table 1. (53)…”
Section: Resultsmentioning
confidence: 99%